2009
DOI: 10.1242/jeb.022111
|View full text |Cite
|
Sign up to set email alerts
|

Yolk androgens and the development of avian immunity: an experiment in jackdaws (Corvus monedula)

Abstract: SUMMARYMaternally derived androgens have been shown to influence offspring phenotype in various ways. In birds, the benefits of prenatal androgen exposure, such as increased competitiveness and accelerated growth in nestlings, have been suggested to be balanced by costs, such as reduced immune function. In this study, we used an integrative approach to examine the influence of yolk androgens on the development of immune function in jackdaw (Corvus monedula) nestlings. Specifically, we tested whether the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 56 publications
2
38
0
1
Order By: Relevance
“…Such effects include suppression of immune responsiveness, at least in the short term, when in ovo testosterone is experimentally increased (e.g. Müller et al, 2005;Navara et al, 2005;Sandell et al, 2009) and when natural variation in nestling testosterone is examined (López-Rull et al, 2010). The underlying cause of immune suppression by yolk testosterone may be a trade-off between resources allocated to two energetically expensive physiological tasks: growth (increased by androgens) and immune-system use and maintenance (decreased by androgens) (Sheldon and Verhulst, 1996;Lochmiller and Deerenberg, 2000); however, this has by no means been clearly established as the sole cause (reviewed in Groothuis et al, 2005;Gil, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Such effects include suppression of immune responsiveness, at least in the short term, when in ovo testosterone is experimentally increased (e.g. Müller et al, 2005;Navara et al, 2005;Sandell et al, 2009) and when natural variation in nestling testosterone is examined (López-Rull et al, 2010). The underlying cause of immune suppression by yolk testosterone may be a trade-off between resources allocated to two energetically expensive physiological tasks: growth (increased by androgens) and immune-system use and maintenance (decreased by androgens) (Sheldon and Verhulst, 1996;Lochmiller and Deerenberg, 2000); however, this has by no means been clearly established as the sole cause (reviewed in Groothuis et al, 2005;Gil, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, cell-mediated and humoral immunity were found to be reduced in black-headed gull chicks (Larus ridibundus) that had been exposed to high levels of androgens in the egg (Groothuis et al 2005a;Müller et al 2005). A similar reduction in both branches of the immune system was found in jackdaws (Corvus monedula; Sandell et al 2009). In the same line, experimentally infected house martins (Delichon urbica) and great tits (Parus major) laid eggs with lower androgen levels than control birds (Tschirren et al 2004;Gil et al 2006), although a recent study failed to find an effect after a similar experimental approach (Heylen et al 2012).…”
Section: Introductionmentioning
confidence: 81%
“…Indeed, theory predicts that benefits derived from high androgen levels are counteracted by negative effects on immunity (Folstad and Karter 1992). In the case of yolk androgen levels, several studies have found support for this hypothesis, in both the cellular and humoral axes of immunity (Müller et al 2005;Groothuis et al 2008;Sandell et al 2009). However, other studies have found no effects (Rubolini et al 2006b) or conflicting evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of the nestlings was 18 days (10-26). After taking a plasma sample at primary sampling, we injected naïve nestlings with 200 ll of tetanus-diphtheria vaccine (Mérieux, 500 ll containing 20 IE tetanus and 2 IE diphtheria toxoids) in the pectoral muscle (Råberg et al 2000;Sandell et al 2009). Seven days later, the nests were climbed again, and a second blood sample was taken, from which plasma was extracted and stored at -20°C.…”
Section: Specific Antibody Response Testmentioning
confidence: 99%